Synthesis of Ruthenium Metathesis Catalysts: Small Cyclic (Alkyl)(Amino)Carbene and Fluorophore-Tagged Ligands for Frontier Applications in Olefin Metathesis - da Silva, Pedro (Université d'Ottawa / University of Ottawa, 2024)
Olefin metathesis has emerged as a versatile tool with important potential applications in the production of pharmaceuticals, specialty polymers, and crucial building-block chemicals from biomass sources. Ruthenium metathesis catalysts shine in these contexts, due to their remarkable functional-group tolerance and superior resistance to moisture and oxygen compared to catalysts based on earlier transition metals. Nevertheless, deployment of molecular olefin metathesis catalysts on the scale required for industrial production has been hampered by low catalyst productivity. Increased productivity has been achieved by the incorporation of cyclic (alkyl)(amino)carbene (CAAC) stabilizing ligands. Targeted in this thesis work was the adaptation of CAAC catalysts to better enable metathesis of internal olefins. Even the cis-configured olefins present in plant or algal oils are more challenging than 1-olefin substrates, owing to their greater steric hindrance. Efforts were undertaken to enhance catalyst performance by reducing the bulk of the CAAC ligand. Indeed, this approach is expected to be broadly relevant to the metathesis of internal olefins and other crowded substrates. The first part of this thesis explores the challenges in preparing Hoveyda-type catalysts of the general form RuCl₂(CAAC)(=CH₂C₆H₄-𝜊-OⁱPr), in which small CAACs are present. Specifically targeted was a complex containing the smallest current CAAC ligand, in which the carbene carbon is flanked by an N-mesityl group and a dimethyl-substituted carbon. Meagre yields in the synthesis of this catalyst have been achieved to date, with a maximum of 14% in the open literature. Acting on the hypothesis that a major, overlooked problem lies in abstraction of the [Ru]=CHR ligand by free CAAC or PCy₃ present during catalyst synthesis, a new route was established via ligand exchange of the RuI₂(PCy₃)(=CH₂C₆H₄-𝜊-OⁱPr) platform with the small CAAC indicated above. The bulk of the iodide ligands inhibits nucleophilic attack at the benzylidene, conferring the necessary steric protection to prevent catalyst decomposition. Ensuing halide exchange then afforded access to the desired chloride catalyst. This strategy was successful, giving access to the target complex in 55% yield. It offers a potentially generalizable methodology for the preparation of ruthenium metathesis catalysts bearing small stabilizing ligands. Also examined was the synthesis of a fluorophore-tagged olefin metathesis catalyst. Such catalysts are of interest for their potential to enable real-time monitoring of catalyst behaviour at concentrations too low for NMR analysis. While challenges remain in optimizing yields in the synthesis of a known dansyl-tagged catalysts, the methodology developed (particularly the synthesis of a dansyl-tagged benzylidene) provides a solid foundation for future advances. In sum, this thesis presents advances in the synthesis of designed catalysts for frontier applications in olefin metathesis. Ruthenium catalysts bearing small CAAC ligands and fluorophore tags are anticipated to enable new applications and new insights relevant to materials science, renewable feedstocks, and process chemistry.
Keywords: olefin metathesis; cyclic (alkyl)(amino)carbenes; catalyst decomposition; self-metathesis; fluorophore-tagged; dansyl